Recovering sovereignty over natural resources: The cases of Bolivia and Ecuador - Humberto Campodónico Sánchez (South Centre, 2016)
This document analyzes the renegotiation process of oil and gas contracts in two Latin American countries, Bolivia and Ecuador, from 2003 to 2010 and the measures taken for sectorial policy reform in the hydrocarbon sector and our conclusions are that it has been favourable. Section I provides the general framework of the situation of the hydrocarbon sector in Latin American countries and a section of Synthesis and Conclusions of the study. Section II analyses the nationalization of the hydrocarbon sector in Bolivia from 2002 to 2010. Section III analyses Ecuador's new Constitution of 2008 and the renegotiation of the hydrocarbon contracts. Finally, we present three Annexes: Annex 1 describes the arbitration cases of Ecuador and private companies at the International Centre for Settlement of Investment Disputes (ICSID). Annex 2 and 3 present briefly the views of the International Monetary Fund (IMF) about the overall performance of Bolivia and Ecuador. The challenge of transforming natural resource rich economies and moving away from heavy dependence on commodities is not a short-term process. In spite of the advances made by these economies, they still rely heavily on commodities, a process that will have bigger problems now that the super cycle of high commodity prices has come to an end.
Keywords: 300; Rohstoffreichtum; Souveränität; Energiewirtschaft; Regulierung; Internationale Schiedsgerichtsbarkeit; Ecuador; Bolivien